Liver function tests in chronic viral hepatitis cases - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
The liver has many vital functions and biochemical tests are used for the assessment. For the diagnosis of chronic hepatitis: (1) persistence of increased alanine aminotransferase (ALT) for 6 months after an episode of acute hepatitis

or (2) increased ALT (without another explanation) on more than one occasion over a period of 6 months are needed. The time period may be shorter for the patients with risk factors. Although the clinical picture of HBV and HCV in chronic cases is similar, aminotransferase activities are different. In HBV, ALT activity is generally constant, except increases are evident at seroconversion times. On the other hand, two-third of HCV cases experience fluctuation. In the evaluation of a patient with a new diagnosis of chronic viral hepatitis, a comprehensive medical history should be taken, followed by full physical examination. Laboratory workup should start with a comprehensive metabolic panel with liver function tests including assessment of synthetic function with prothrombin time and serum albumin level measurement. Screening for the chronic hepatic injury is not cost-effective and should be limited to high-risk individuals. ALT should be the preferred biochemistry parameter besides viral serology and increased activity should be confirmed before further evaluation. For treatment, patients with increased ALT are more likely to respond than those with initially normal ALT activity.
Keywords: Chronic viral hepatitis; Hepatitis B virus; Hepatitis C virus; Alanine aminotransferase; Aspartate aminotransferase